Divine Universal Causality and the Particular Problem of Hell: A Quiescence Solution - Wood, Adam (Scientia et Fides, 2021)
I call the Particular Problem of Hell (PPH) the problem of explaining why God allows a certain set of created persons to populate hell, as opposed to allowing some other set of created persons to do so. This paper proposes a solution to PPH on behalf of proponents of Divine Universal Causality (DUC) — the view, roughly, that God causes everything distinct from himself to exist at any time it exists. Despite initial appearances, I argue, proponents of DUC can adopt a version of the popular approach to the Problem of Hell sometimes called the Choice Model. My proposal is based upon Eleonore Stump’s Thomistically-inspired notion that our wills can enter a state of "quiescence" with respect to a given option. While proponents of DUC will, I argue, most likely find Stump’s own quiescence-based solution to PPH unacceptable, there is a way of modifying her approach that renders it compatible with God’s causing everything distinct from himself, including the free choices of his creatures.